Procedure for Handling 4-H Accounts: Tax-Related Procedures for 4-H Clubs and Affiliated Groups - Marilyn N. Norman; Joy C. Jordan (EDIS)
4H5.7, a 3-page factsheet by Marilyn N. Norman and Joy C. Jordan, details correct tax procedures for 4-H clubs. Includes information on exemptions, state tax, and getting on the IRS list of charitable organizations. Published by the UF Department of Family, Youth and Community Sciences, February 2007.